Risk Factors Affecting HIV Cases at the 2023 Medan City Exemplary Health Center - Simanjuntak, Imran; Asriwati, Asriwati; Nasution, Ramadhani Syafitri (PROMOTOR, 2025)
The cumulative number of ODHIV (People with HIV) in Indonesia based on SIHA (HIV AIDS Information System) data reported as of March 2022 is 329,581 people. At the Teladan Medan Health Center, the number of HIV cases has increased every year. Where from 2019 to 2021 HIV cases at the Teladan Health Center reached 600 people who had routinely received ARV therapy and in 2023 there was an increase of 290 people to 890 people who had routinely received ARV therapy. Sexually transmitted infections, family history of diseases, socioeconomic circumstances, blood transfusions, homosexuality, heterosexuality are risk factors that affect the incidence of HIV. The researcher's goal is to find out the risk factors that affect HIV cases at the 2023 Medan City Health Center. Methods: Using observational analytical methods using a Case Control research design. The sample amounted to 148 respondents, 74 case groups and 74 control groups were taken by consecutive sampling. Data analysis was carried out univariate, bivariate and multivariate with logistic regression tests. The results of the study on the analysis of the bivariate test with chi-square showed factors that affected the incidence of HIV, namely the history of sexually transmitted infections p = 0.034, family disease history p = 0.021, socioeconomic status p = 0.045, drug p = 0.042, blood transfusion p = 0.024, homosexual p = 0.014, and heterosexual p = 0.029 against the incidence of HIV at the 2023 Medan City Teladan Health Center. Meanwhile, the multivariate test found that the most influential factor with the incidence of HIV was more than one sex habit variable (p= 0.001; Exp(B) 3,920). Conclusion The dominant risk factor affecting the incidence of HIV cases at the Medan City Health Center is the habit of having more than one. suggestions to improve promotive preventive services about the dangers of HIV, the factors that cause HIV, and create a culture of loyalty to couples and also demonstrate the issue of the dangers of HIV both among the community and students.